2012
DOI: 10.1364/ol.37.002322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infiltration pressure on the birefringent properties of a side-hole fiber filled with indium

Abstract: The effect of the infiltration pressure on the birefringent properties of a side-hole fiber filled with indium was investigated by the fiber-optic Sagnac loop interferometry. The fiber was made at the various gas pressures during the metal infiltration process. It was found that the birefringence of the fiber strongly decreased from 5.55×10(-4) to 1.68×10(-4) with the increase of the pressure from 15 to 45 bars, due to the compensation effect of the pressure applied during the infiltration. The temperature dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is interesting that the sign of B s changed from positive to negative near 55°C. This unique birefringence property can be explained by the compensation effect between the tensile stress from the thermal expansion of indium (positive effect to the birefringence) and the compressive stress from the applied gas pressure during the indium infiltration process (negative effect to the birefringence) [18]. The positive effect on the birefringence by the thermal property of indium decreased with the increase of temperature while the negative effect on the birefringence by the applied gas pressure did not change regardless of temperature; thus the birefringence became negative at a temperature near 55°C.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that the sign of B s changed from positive to negative near 55°C. This unique birefringence property can be explained by the compensation effect between the tensile stress from the thermal expansion of indium (positive effect to the birefringence) and the compressive stress from the applied gas pressure during the indium infiltration process (negative effect to the birefringence) [18]. The positive effect on the birefringence by the thermal property of indium decreased with the increase of temperature while the negative effect on the birefringence by the applied gas pressure did not change regardless of temperature; thus the birefringence became negative at a temperature near 55°C.…”
Section: Resultsmentioning
confidence: 99%
“…This anomalous behavior is quite different from conventional-like fibers with two holes filled with In, in which, for low infiltration pressures, the birefringence decreases linearly with the temperature. In contrast, for high infiltration pressures (>20 bar), the birefringence decreases linearly at low temperatures (18.5 °C−54.5 °C), after which the decrease becomes nonlinear, saturating at 60 °C without further increases [15]. For this case, we found that the temperature sensitivities of the birefringence differed in the low-temperature region, −5 × 10 −6 C −1 and −7.5 × 10 −6 C −1 for 1310 nm and 1550 nm, respectively.…”
Section: Methodsmentioning
confidence: 93%
“…This behavior is quite different from conventional-like fibers with two holes filled with indium which, in the case of low infiltration pressures, the birefringence decreases linearly with the temperature, whereas in the case of high infiltration pressures (>20 bar), the birefringence decreases linearly at low temperatures (18.5-54.5 C), after which the decrease becomes nonlinear, saturating from 60 C without further increases. 13 When heat is transferred to the PCF, the metal expands and squeezes the fiber microstructure. As a result of the photoelastic effect, stress induces anisotropic changes of refractive index within the fiber and thus modifies the residual birefringence in the fiber.…”
mentioning
confidence: 99%